Effect of Water Stress on the Seedlings Growth of Acacia Tortilis Subsp. Raddiana in Nursery in Sahelian Zone, Niger - Yandou, Ishmael Bio; Rabiou, Habou; Soumana, Idrissa; Laouali, Abdou; Mahamane, Ali (European Scientific Journal, ESJ, 2020)
The characteristic dominance of Acacia tortilis species in the Sahel plays a major ecological and economic role for its populations. However, in recent years, the high pastoral pressure has compromised the natural regeneration of the species and it becomes therefore important to investigate the effect of substrate and water stress on the growth of A. tortilis plants in nurseries. An experimental design made of 72 seedlings divided into 4 treatments with different proportions of substrate and watering was put in place. During the six months study, 3 seedlings were destroyed every month, and growth parameters were measured. These include the height, diameter at the collar, pivot length and diameter, number and length of lateral roots, number of nodes, number of branches, number of leaves and number of spines. Results show that the height, the collar diameter, the pivot diameter, total number of roots, number of lateral roots, number of branches, number of leaves are significantly different among treatments. The substrate containing 1/4 manure and 3/4 sand + watering twice a day recorded the best growth height (112.1±4.4 cm); number of branches (39.3±24.2); leaf biomass (301.67±97.99 g) and total number of roots (34±1.7) after 6 months of followup. The average root pivot length of Tr4 treatment seedlings (115.5±18.2 cm) is 4 times greater than their average height during the 6-month follow-up. The average root pivot length of Tr4 treatment seedlings is 4 times greater than their average height during the 6-month follow-up. After 3 months in nursery, the substrate containing sand only + watering once a week ensures a good development of the rooting root system to young seedlings, allowing them to better explore soil horizons. Hence, for a reforestation program, the substrate containing sand only + watering once a week is the best suited.